2023
DOI: 10.1002/pmic.202200078
|View full text |Cite
|
Sign up to set email alerts
|

Blood proteome of acute intracranial hemorrhage in infant victims of abusive head trauma

Abstract: Abusive head trauma (AHT) is a leading cause of mortality and morbidity in infants.While the reported incidence is close to 40 cases per 100′000 births/year, misdiagnoses are commonly observed in cases with atypical, subacute, or chronic presentation.Currently, standard clinical evaluation of inflicted intracranial hemorrhagic injury (ICH) in infants urgently requires a screening test able to identify infants who need additional investigations. Blood biomarkers characteristic of AHT may assist in detecting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…We focused on the five complement proteases (e.g. C1S, C1R, C2, C1RL, MASP1, Figure S2A ) that were significantly elevated in sera from severe AHT cases and for which expression levels were measured in our previous study[19]. We observed that proteolytic activities of five complement proteases did not follow their high circulating levels or correlate with markers of neuronal damage (i.e.…”
Section: Article Type: Rapid Communicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…We focused on the five complement proteases (e.g. C1S, C1R, C2, C1RL, MASP1, Figure S2A ) that were significantly elevated in sera from severe AHT cases and for which expression levels were measured in our previous study[19]. We observed that proteolytic activities of five complement proteases did not follow their high circulating levels or correlate with markers of neuronal damage (i.e.…”
Section: Article Type: Rapid Communicationsmentioning
confidence: 99%
“…We then focused in the activity of serine proteases of complement cascade involved in neuroinflammation [7] and metabolic serine lipases highly expressed in brain [13]. As biochemical reactions occur at controlled stoichiometric proportions, we hypothesized that after the blood has clotted, the native serum liquid, that is free of additives, potentially contains the active proteases of complement if the latter were present in excess in the bloodstream, as we previously demonstrated in infants with intracranial bleeding induced by AHT [19]. We focused on the five complement proteases (e.g.…”
Section: Article Type: Rapid Communicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 1684 differential phosphosites together with 25 phosphorylation motifs were identified, indicating a role of Akt1 in TRAIL signaling. While the four articles above interrogated the proteomic and phosphoproteomic regulations in a defined clinical phenotype or a clarified drug response, the fifth article in this category by Wiskott et al [17], very interestingly, was set to identify blood biomarkers for the acute intracranial hemorrhage in infant victims of abusive head trauma (AHT), a status that is difficult to be effectively diagnosed in current hospital practice. The authors measured the matched postmortem and antemortem blood specimens of AHT cases, together with controls of sudden infant death syndrome using DIA‐MS.…”
mentioning
confidence: 99%